A mechanistic computational model of HGF-VEGF-mediated endothelial cell proliferation and vascular permeability - Rebeca Hannah de Melo Oliveira; Akash Patil; Brian H. Annex; Arvind P. Pathak; Aleksander S. Popel (iScience)
Summary: Hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF) are important pro-angiogenic factors in angiogenesis-dependent diseases. While sharing some signaling pathways, their contrasting effect on vascular permeability remains under investigation. To explore how these factors promote angiogenesis, we developed, calibrated, and validated a data-driven mechanistic computational model of HGF and VEGF signaling in endothelial cells (ECs). We proposed that variations in permeability profiles may stem from RAC1-PAK1 activation via site-specific phosphorylation. By introducing permeability and proliferation indices, our simulations indicated a dose-dependent effect of VEGF that hampered the ability of HGF to promote vascular stability. Our simulations indicate that HGF did not require VEGFR2 activation to affect permeability and proliferation. This model has the potential to be applicable and helpful in analyzing angiogenesis-dependent diseases. It provided insights into the mechanisms of EC proliferation and vascular permeability induced by HGF and VEGF and permitted evaluation of their separate or combined effects.